Facing Academic Stress: The Role of Hardiness and the Moderating Effect of Social Support in Psychology Students - Agita Nova Purba; Meutia Nauly; Lita Hadiati (Psikostudia : Jurnal Psikologi, 2025)
Master's degree students in professional psychology are vulnerable to experiencing constraints and obstacles during their educational journey, which can lead to the emergence of academic stress. This study aims to investigate the role of social support in moderating the relationship between hardiness and academic stress among master's degree students in professional psychology. Accidental sampling, which is a nonprobability sampling technique, is used in the sampling method. The participants consisted of 225 master's degree students in professional psychology in Indonesia who were currently enrolled in the Praktik Kerja Profesi Psikologi (PKPP) and/or Thesis. The research instruments utilized three scales: the academic stress scale, the hardiness scale, and the social support scale. The data were analyzed using moderation regression analysis. The findings of the study indicate that (1) there is an influence of hardiness on academic stress among master's degree students in Professional Psychology, (2) there is an influence of social support on academic stress among master’s degree students in Professional Psychology, and (3) Social support weakens the influence of the relationship between hardiness and academic stress on students of Master Psychology Professions. Mahasiswa Magister Psikologi Profesi rentan mengalami kendala dan hambatan selama proses menempuh pendidikan yang dapat mengakibatkan munculnya stres akademik. Penelitian ini bertujuan untuk mengetahui apakah terdapat peran dukungan sosial dalam memoderasi hardiness terhadap stres akademik pada mahasiswa Magister Psikologi Profesi. Accidental sampling, yang merupakan teknik nonprobability sampling, digunakan dalam metode pengambilan sampel. Partisipan dalam penelitian ini berjumlah 225 mahasiswa Magister Psikologi Profesi di Indonesia yang sedang mengikuti mata kuliah Praktik Kerja Profesi Psikologi (PKPP) dan/atau Tesis. Alat ukur penelitian menggunakan tiga skala yaitu skala stres akademik, skala hardiness dan skala dukungan sosial. Teknik Analisa data yang digunakan yaitu analisis regresi moderasi. Hasil penelitian menunjukkan bahwa (1) Terdapat pengaruh hardiness terhadap stres akademik pada mahasiswa Magister Psikologi Profesi, (2) Terdapat pengaruh dukungan sosial terhadap stres akademik pada mahasiswa Magister Psikologi Profesi, dan (3) Dukungan sosial memperlemah pengaruh antara hubungan hardiness terhadap stres akademik pada mahasiswa Magister Psikologi Profesi.